A Critical Review of Supply Chain Security in India and Total Quality Management in Supply Chain Security Context - Jain, Ashish (2010)
Today supply chain security has become an important aspect for Operations Management and other important businesses. Whether it is trade facilitation, regulatory compliances or import-export business it has earned a significance importance. The research comprises of a thorough review on supply chain, its security and quality management techniques. Since, the last decade security has gained significant importance in the supply chain and organizational activities, so it is interesting to talk about various standards and security procedures in different countries. As, the emergence of security has increased, it is better to understand and incorporate total quality management techniques into supply chain security. Quality techniques like TQM and Six Sigma are very much related and connected to security development.